IKLAN MASA KOLONIAL 1930 - 1942 TINJAUAN SOSIOHISTORIS - Baskoro Suryo Banindro (DeKaVe, 2011)
Dutch colonial culture that come to enrich the culture of Indonesia, it joined the growing culture of modern Indonesia, it can be observed through the lifestyles of people and uptake of aesthetic value. Graphic design style developed in the colonial Indies Dutch East Indies and had peaks in the artistic developments of the 1930s. The design style developed by Dutch graphic designer is a blend of modern design style that flourished in Europe early 20th-century art with a product of local culture. The combination has created a style of indie that became a source of inspiration for creativity designer graphic design of the future. Advertising colonial period in Indonesia, developed along with the progress of knowledge, especially in the fields of economy and industry, idiom - idioms unsure that are tailored to its target audience. In the context of social phenomena and the idea of ??modern advertising in Indonesia now, of course, inseparable from the history of the Dutch East Indies colonialism itself.Keyword: Advertising colonial period, westernization, a zeitgeist